2016
DOI: 10.1017/s1368980016001002
|View full text |Cite
|
Sign up to set email alerts
|

Role of family support and women’s knowledge on pregnancy-related risks in adherence to maternal iron–folic acid supplementation in Indonesia

Abstract: Improving women's knowledge of pregnancy-related risks and involving family members, particularly the husband and importantly for less-educated women, improved adherence to IFA supplementation. ANC visit opportunities must be optimized to provide women with sufficient numbers of IFA tablets along with health information (especially on pregnancy-related risks) and partner support counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 32 publications
(73 reference statements)
9
37
0
Order By: Relevance
“…Although this is below the recommended levels, it is substantially better than the current situation (approximately 40 IFA tablets are consumed during pregnancy). Our findings align well with existing literature from Bihar, Pakistan, Indonesia, and Kenya related to associations of maternal knowledge and family support in ensuring sustained IFA adherence (Birhanu et al, ; Wiradnyani, Khusun, Achadi, Ocviyanti, & Shankar, ). Prior research also highlights the role of education and wealth for compliance to IFA recommendations (Nisar, Dibley, & Mir, ; Wendt et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Although this is below the recommended levels, it is substantially better than the current situation (approximately 40 IFA tablets are consumed during pregnancy). Our findings align well with existing literature from Bihar, Pakistan, Indonesia, and Kenya related to associations of maternal knowledge and family support in ensuring sustained IFA adherence (Birhanu et al, ; Wiradnyani, Khusun, Achadi, Ocviyanti, & Shankar, ). Prior research also highlights the role of education and wealth for compliance to IFA recommendations (Nisar, Dibley, & Mir, ; Wendt et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In a community-based randomized controlled trial in rural Pakistan, education of pregnant women and their husbands on safe motherhood resulted in a higher intake of iron supplements, an improvement of diet, and a lower workload during pregnancy than in the control group ( 45 ). With the use of data from 3 rounds of the Demographic and Health Survey, a study in Indonesia reported a significant association between husband support and adherence to IFA supplementation during pregnancy (which was twice that in households in which husbands were supportive) ( 14 ). A randomized controlled trial in Kenya also showed a positive impact on calcium adherence among pregnant women who had an adherence partner, 52% of whom were husbands ( 23 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines recommend that, in addition to receiving specific micronutrient supplements and balanced energy and protein dietary supplementation (in food-insecure areas), women should receive relevant and timely counseling about healthy diets, physical activity, and adequate weight gain during pregnancy. To date, most large-scale nutrition interventions in developing countries either focus on specific micronutrient supplementation ( 7–11 ) or balanced energy and protein supplementation ( 3 , 12 ) and solely target women of childbearing age without regard for their autonomy within the household and their ability to adopt the promoted behaviors on their own ( 13 , 14 ). Engaging husbands, especially when they are the head of the household and primary decision makers on family health care, is important to improve care-seeking for women and children ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…WRA do not make decisions about their health in isolation; social networks can influence behaviors and family members play a crucial role in supporting the use of IFA tablets in women 38 . Pregnant women whose spouses actively participated in antenatal visits were more likely to demonstrate a significantly higher adherence to IFA supplements than women whose husbands were not active throughout antenatal visits 39 . Mothers and mothers-in-law can also influence the intake and adherence of IFA in pregnant women, even more than their partners as demonstrated by a formative research study among pregnant women in Bangladesh.…”
Section: Introductionmentioning
confidence: 93%